The Role of Sustainable Competitiveness Indicator in Malaysian Tourism and Economic Growth - Soh, Ann Ni; Puah, Chin Hong; Mohammad Affendy, Arip; Jong, Meng Chang (Sciendo, 2024)
This paper proposes a sustainable competitiveness indicator for the state of tourism vulnerability in the Malaysian tourism market. Further investigation has also been done on the timefrequency and lead-lag relationship of the indicator with tourism development and economic growth. The resultant indicator is consisted of 12 variables, identified based on the pillars of sustainability and competitiveness to extract a common vulnerability component using a dynamic approximate factor model. The model’s accuracy rate was at a promising 92% based on the variable importance assessment using random forest algorithms. Through the implementation of bivariate wavelet coherence analysis, the empirical results indicated that the constructed indicator has a positive leading role in Malaysian tourism development and economic growth. This indicator can be embedded within an early warning system to signify vulnerabilities in the Malaysian tourism market.